E-plane waveguide bandpass filters with wide stopband (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2020)
Introduction. The results of the development of E-plane waveguide bandpass filters with improved selectivity in the stopband are presented. The significant expansion of the stopband and the increase of the attenuation in it was achieved by using of  the stepped-impedance resonators (SIR), the planar implementation of which was proposed in this work for the first time. The successful application of the above mentioned resonators in the designs of E-plane waveguide filters was possible by careful study of the properties of SIRs, which revealed the features of their topology and the possibility of their effective calculation. The topology of hybrid integrated circuits (HIC) of E-plane waveguide SIR filters is proposed, and the procedure of their fast calculation is demonstrated by the example of a two-resonator filter. The measured characteristics of the calculated and fabricated samples of the resonator and filter have shown good agreement with the simulation results.The development of HIC SIR filters. The development is based on the investigated properties of stepped-impedance resonators. The characteristics of these resonators are analyzed in three steps. First, the model of the resonator was constructed in terms of the circuit theory without taking into account the diffraction corrections responsible for changing in slot width of the SIR sections, but taking into account the forming reactances. It is revealed that the obtained characteristics only qualitatively coincide with the results of the second stage of analysis of the resonator, on which its topology, as a whole, was treated with FDTD simulator. In particular, the results obtained in terms of circuit theory do not describe the significant difference in the section length of the resonator required to achieve the maximum spacing of its resonant frequencies and the appearance of a transmission zero in the frequency band between them. At the same time, the improvement of this model, performed in the third stage of the SIR analysis, showed the ability to calculate the characteristics of the resonator with this model, which is necessary for the synthesis of the multi-resonator filter. In addition, a comparative analysis of the single-mode and accurate characteristics of the resonator provided an opportunity to explain the appearance of the above mentioned attenuation pole and to identify the factors affecting its position on the frequency axis. The results obtained in the study of SIRs were successfully used in the calculation of a two-resonator SIR filter with the proposed topology. The synthesis of the filter based on the method using K-inverters. This approach made it possible to quickly obtain the initial values ​​of the filter topology element sizes. These sizes almost did not require refinement when optimized by electrodynamics  simulator. The simulation results of the filter characteristics coincide with the measurement results for the fabricated samples of the resonator and filter with sufficient to practice accuracy.Summary. The proposed topology of E-plane waveguide stepped-impedance resonators and filters based on them provides a significant improvement in the selective characteristics of this class of filters - a significant expansion of the stopband and increase the attenuation in it. The structure of the filter itself is a hybrid integrated circuit that provides high precision of its manufacture and repeatability of the characteristics of the filters without any operations on tuning the samples. In addition, E-plane waveguide technology enables these filters to be used in the millimeter waves range without significantly performance degradation.